Validation of Modified Objective Prognostic Score in Patients with Advanced Cancer in Taiwan - Yusuke Hiratsuka; Sang-Yeon Suh; Seok Joon Yoon; Shao-Yi Cheng; Sung-Eun Choi; Sun Hyun Kim; David Hui; Ping-Jen Chen; Hsien-Liang Huang; Jen-Kuei Peng; Masanori Mori; Takashi Yamaguchi; et al. (Palliative Medicine Reports)
Background: Modified versions of the Objective Prognostic Score (mOPS) needs to be validated to reflect practical palliative care circumstances in Taiwan. Objectives: We compared the abilities of an mOPS score of 1.5 or higher versus a Karnofsky Performance Status (KPS) score of 30 or lower to predict 2-week mortality in patients with advanced cancer in Taiwan. Design: Observational study. Setting/Subjects: We performed a secondary analysis of an international multicenter cohort study of patients in East Asia. Participants were inpatients with advanced cancer in palliative care units (PCUs) in Taiwan. Measurements: We compared the mOPS-B model, which does not require laboratory tests, with the KPS in a 2-week survival timeframe. We compared the accuracy of the prognostic models using sensitivity, specificity, and area under the receiver operating characteristic curve (AUROC). Calibration plots and net reclassification indices (NRI) for 2-week survival were compared between the two models. Differences in survival between the higher- and lower-scoring groups of each model were identified using the log-rank test. Results: We included 317 patients, with a median survival of 14.0 days. The mOPS-B had a high sensitivity (0.82) and high AUROC value (0.69). By contrast, the KPS demonstrated good sensitivity (0.77) and an acceptable AUROC value (0.65) for predicting 2-week survival. The calibration plot did not demonstrate satisfactory agreement between the actual and predicted survival times in either the mOPS-B or the KPS groups. Our NRI was positive (absolute value: 22%), indicating that mOPS-B predicted 2-week survival better than KPS. Conclusions: The mOPS-B may serve better than the KPS as a screening tool for admission to PCUs in Taiwan because it was more accurate at predicting 2-week survival.